Response of Multiple Tissues to Drought Revealed by a Weighted Gene Co-Expression Network Analysis in Foxtail Millet [Setaria italica (L.) P. Beauv.] - Zhang, Renliang; Zhi, Hui; Li, Yuhui; Guo, Erhu; Feng, Guojun; Tang, Sha; Guo, Weixia; Zhang, Linlin; Jia, Guanqing; Diao, Xianmin (Frontiers in Plant Science, 2022)
Characterization of drought-tolerance mechanisms during the jointing stage in foxtail millet under water-limited conditions is essential for improving the grain yield of this C4 crop species. In this trial, two drought-tolerant and two drought-sensitive cultivars were examined using transcriptomic dissections of three tissues (root, stem, and leaf) under naturally occurring water-limited conditions. We detected a total of 32,170 expressed genes and characterized 13,552 differentially expressed genes (DEGs) correlated with drought treatment. The majority of DEGs were identified in the root tissue, followed by leaf and stem tissues and the number of DEGs identified in the stems of drought-sensitive cultivars was about two times higher than the drought-tolerant ones. A total of 127 differentially expressed transcription factors (DETFs) with different drought-responsive patterns were identified between drought-tolerant and drought-sensitive genotypes (including MYB, b-ZIP, ERF, and WRKY). Furthermore, a total of 34 modules were constructed for all expressed genes using a weighted gene co-expression network analysis (WGCNA), and seven modules were closely related to the drought treatment. A total of 1,343 hub genes (including RAB18, LEA14, and RD22) were detected in the drought-related module, and cell cycle and DNA replication-related transcriptional pathways were identified as vital regulators of drought tolerance in foxtail millet. The results of this study provide a comprehensive overview of how Setaria italica copes with drought-inflicted environments during the jointing stage through transcriptional regulating strategies in different organs and lays a foundation for the improvement of drought-tolerant cereal cultivars through genomic editing approaches in the future.